HUBUNGAN PAPARAN KEBISINGAN, PENGGUNAAN ALATPELINDUNG DIRI, MASA KERJA, DAN KARAKTERISTIK INDIVIDU TERHADAP PENINGKATAN TEKANAN DARAHPADA PEKERJA DI PT X TAHUN 2017 - Puspita Kurnia Wangi (2017)
Hypertension is a disease that could develop progressively but does not always have any symptomps. Various risk factors of hypertension are found in everywhere including in the work environment. The existence of a potential hazard in daily life could be a risk factor that affects worker's health. Noise is one of the physical hazards that can affect blood pressure and is a risk factor for hypertension. This study aims to determine the relationship between noise exposure, working period, use of PPE, and individual characteristics with the increased blood pressure on PT.X workers in 2017. This study is analytic study with cross sectional design. A total of 104 workers is taken with simple random sampling technique. Independent variables for this study are noise exposure, working period, individual characteristics, and the use of PPE. Bivariate analysis using Chi-Square test showed that there were significant differences between noise intensity, BMI, and smoking in workers with increased blood pressure and workers with no increased blood pressure (p<0.05). In the multivariate analysis, noise intensity (p=0.001), BMI (p=0.001) and smoking (p=0.006) were independent predictors for the incease of blood pressure